(untitled) (Global Journal of Medical Research, 2024)
Aim To provide insight into the importance of nursing and para medical competencies to act from Positive Health in order to contribute to greater health well-being and a healthier lifestyle for patients Design This position paper will describe the aim the first results and the coming focus of the professorship of Positive Health Lifestyle and leadership Methods We used several methods like depth interviews and focus groups with about 30 patients most cardiology and rheumatology and about 30 professionals most nurses and para medics incardiology and rheumatology and a cardiologicpatient journey to determine what is necessary for nurses and para medics to act from Positive Health All studies were approved by the Institutional Review Board and the attributes benefits and uses of the studies were explained to all participants and informed consent was obtained Results There is still too little attention for lifestyle and hardly for sustainable behavioural change Communication and leadership competencies and multidisciplinary collaboration are essential in this Conclusion Applying Positive Health requires a transformation of the healthcare system and the healthcare professionals themselves More knowledge is needed about the competencies of nurses and para medics to act from Positive Health Implications for the Profession and or Patient Care A toolbox of tools will be created based on practice-oriented research with ways to increase the competencies of healthcare professionals and to act more from Positive Health By encouraging healthcare professionals to think and act differently based on Positive Health we hope to promote patients self-management and intrinsic motivation and thus contribute to a healthier lifestyle Impact An unhealthy lifestyle can lead to various diseases A positive lifestyle change can lead to the prevention reduction or even disappearance of the disease It is important that nurses and para medics pay attention to lifestyle from a broad view of health such as Positive Health In the professorship we develop tools to increase the competencies of nurses and paramedics to act more from Positive Health and integrate lifestyle into daily care and treatment And so towards greater health well-being and a healthier lifestyle No Patient or Public Contribution Introduction I n November 2021 the Lecturer Position at Institutes L INT professorship was established by Saxion and Medical Spectrum Twente and as partners physiotherapy practice Pro-F and the Thoracic Centre Twente with Sandra van Hogen-Koster as a professor With this the first Dutch professorship that focuses on the ideas of Positive Health has been launched Huber et al 2011 introduced a more dynamic concept of health valuing resilience as the ability to adapt and self-manage in the face of social physical and emotional challenges 1 Defining health as complete physical mental and social well-being such as the World Health Organization WHO that does is outdated according to Huber If you stated health so rigidly no one is ever healthy she said Everyone is not completely healthy sometimes so that you should be treated for that That leads to unnecessary and costly medicalization of healthcare according to Huber Positive Health was deliberately not described as a definition but as a general concept intending to be a characterization of a goal to work towards being enhancement of resilience overall health and well-being This concept was further elaborated into Positive Health PH which comprises six dimensions bodily functions mental wellbeing meaningfulness quality of life participation and daily functioning 2 These dimensions are derived from the responses from patients and citizens on the question what they perceived to constitute health 2 Positive Health provides insight into what is important to people and often results in behaviour change this desire for change is in turn regularly indirectly linked to a healthier lifestyle The overarching aim of integrating PH into the healthcare system is to prioritize health over disease and initiate this transformation Applying PH requires a transformation of the healthcare system and the healthcare professionals themselves A toolbox of tools will be developed to increase the competencies of healthcare professionals to act more from PH Where is the professorship now after 2 years what are the first results and what is the focus for the upcoming 2 years This position paper describes the urgency of transforming Healthcare Integrating Positive Health Principles for Enhanced Wellbeing and Lifestyle Change